2017
DOI: 10.5152/npa.2017.18065
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self Report Stress Scale Using Item Response Theory-I: Item Selection, Formation of Factor Structure and Examination of Its Psychometric Properties

Abstract: Results showed that the scale has basic psychometric requirements provided that the scale will be supported by validity studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…The ability of internet-based programs to sustain treatment benefits post-discharge from face-to-face treatment is also established ( Kenter et al, 2015 ). Furthermore, going by the three models of stress- stimulus-based, response-based and transaction-based models ( Papathanasiou et al, 2015 ; Corina et al, 2014 ; Tatar et al, 2018a ), it is expected that the three models could be explained using the ABCDE therapeutic modalities, thereby bringing about relieve on the part of the teachers. The stimulus based model of stress proposes that stress occurs when there is objective activating events (A), called stressors; while response-based model suggest that stress emotional, physiological and behavioral reactions (C) towards the stressor (A).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of internet-based programs to sustain treatment benefits post-discharge from face-to-face treatment is also established ( Kenter et al, 2015 ). Furthermore, going by the three models of stress- stimulus-based, response-based and transaction-based models ( Papathanasiou et al, 2015 ; Corina et al, 2014 ; Tatar et al, 2018a ), it is expected that the three models could be explained using the ABCDE therapeutic modalities, thereby bringing about relieve on the part of the teachers. The stimulus based model of stress proposes that stress occurs when there is objective activating events (A), called stressors; while response-based model suggest that stress emotional, physiological and behavioral reactions (C) towards the stressor (A).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the outcome of this study support previous findings showing that interventions are effective in helping teachers regain control over stressors, reduce the intense psychosomatic symptoms and use effective strategies for dealing with stressful situations associated with teaching. 15,40,45,46,[49][50][51][52][53][54][55] Consequently, an earlier study 56 showed that a positive change in perception of stress can lead to a reduction in physiological and psychological symptoms associated with job stress. This is well conventional in the bREBT viewpoint, which works through opposing negative thoughts, feelings, emotions associated with stressors (occupational environments) and replacing them with more helpful ones.…”
Section: Discussionmentioning
confidence: 99%
“…Many definitions are made for understanding stress and efforts are made to explain it with anthropological, physiological, endocrinological, sociological and psychological approaches. On the other hand, it is reported that the existence of different explanations and approaches creates a confusion and makes it difficult to understand the connections between these approaches (Tatar, Saltukoğlu & Özmen, 2018).…”
Section: Graded Response Model (Grm)mentioning
confidence: 99%
“…The biopsychosocial model (BPS) is presented as an approach that combines these two approaches in a single framework. (Tatar, Saltukoğlu & Özmen, 2018).…”
Section: Graded Response Model (Grm)mentioning
confidence: 99%